2002
DOI: 10.1002/ijc.10496
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine serum levels in soft tissue sarcoma patients: Correlations with clinico‐pathological features and prognosis

Abstract: We investigated the correlations between serum levels of selected proinflammatory, hematopoietic and angiogenic cytokines and soluble cytokine receptors with the clinicopathological features and prognosis in soft tissue sarcoma patients. Serum levels of 9 cytokines (TNF␣, IL-1ra, IL-6, IL-8, IL-10, M-CSF, G-CSF, VEGF, bFGF) and 4 free cytokine receptors (sIL-2R␣, sIL-6R, TNFRI, TNFRII) were measured by means of an enzyme-linked immunoadsorbent assay kit in 156 soft tissue sarcoma patients before the treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
71
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 68 publications
7
71
0
Order By: Relevance
“…Our findings suggest that measurement of levels of angiogenic factors may provide prognostic information. This is consistent with earlier studies in sarcoma and other diseases in which elevated VEGF correlated with higher stage and/or poor outcome (20,51), although in one study of synovial sarcoma a correlation was not observed (53). It remains to be seen whether urinary VEGF levels will useful for predicting or monitoring responses to therapy (22).…”
Section: Discussionsupporting
confidence: 89%
“…Our findings suggest that measurement of levels of angiogenic factors may provide prognostic information. This is consistent with earlier studies in sarcoma and other diseases in which elevated VEGF correlated with higher stage and/or poor outcome (20,51), although in one study of synovial sarcoma a correlation was not observed (53). It remains to be seen whether urinary VEGF levels will useful for predicting or monitoring responses to therapy (22).…”
Section: Discussionsupporting
confidence: 89%
“…Serological study showed that IL-6 has a positive correlation with the progression of various soft tissue sarcomas including MFH. 37 In our recent study, CRP, which directly reflects IL-6, proved to be significantly associated with the malignancy grade, tumor size, and histological subtypes of MFH. 6 These findings indicate that IL-6 may be responsible for its biological behavior; tumor progression, proliferation, and morphology.…”
Section: Discussionmentioning
confidence: 85%
“…Reports in melanoma (13)(14)(15), non-small-cell lung cancer (NSCLC; refs. 16,17), prostate cancer (18), esophageal squamous cell carcinoma (19), soft sarcoma (20) and bone sarcoma (21), renal cell carcinoma (RCC; ref. 22), urothelial tumors (23,24), hepatocellular carcinoma (HCC; refs.…”
Section: Introductionmentioning
confidence: 99%